Caracterização funcional do produto da ORF NCU03043 de Neurospora crassa homólogo ao fator de transcrição FlbC de Aspergillus nidulans - Boni, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The filamentous fungus Neurospora crassa is a model organism widely used for studies of several aspects of the biology in eukaryotes. We have been studying the molecular and biochemical mechanisms involved in glycogen metabolism regulation in this fungus. The screening of a knocked-out strains set in genes encoding transcription factors has identified many proteins likely involved in the regulation of glycogen metabolism in the fungus N. crassa. Among the proteins, the transcription factor FLBC was identified as a regulatory protein of the glycogen metabolism. The mutant strain showed changes in the glycogen accumulated and in the gsn gene expression when compared to the wild-type strain under heat stress. Preliminary studies carried out in our laboratory showed severe morphological changes in the strain flbCKO, such as reduced ability to conidiate, presence of a few microconidia, reduced production of aerial hyphae, altered morphology of hyphae tips, changes in the colonies morphology and high production of the pigment melanin, suggesting that FLBC plays an important role in the fungus development. The transcription factor FLBC, object of study in this work, is the Aspergillus nidulans and Podospora anserina FlbC/FLE1 homologous protein, respectively, both involved in conidiation and fungal growth. The purpose of this study was to perform functional characterization of this transcription factor in N. crassa. Analysis of gene expression showed high levels of the transcript flbC during vegetative growth and after induction of asexual development. The knockout strain presented a misregulation in the accumulation of reserve carbohydrate (glycogen and trehalose) during vegetative growth accumulating higher levels of both carbohydrates as compared to the wildtype strain. Analysis of gene expression in the strains wild-type and flbCKO showed that gdn (encoding for debranching enzyme) and gpn (encoding glycogen phosphorylase) genes are...

O fungo filamentoso Neurospora crassa é um organismo modelo amplamente utilizado para estudos de diversos aspectos da biologia dos eucariotos. Nosso laboratório tem utilizado este fungo para estudar os mecanismos moleculares e bioquímicos envolvidos na regulação do metabolismo de glicogênio. A avaliação de uma coleção de linhagens mutantes individualmente nocauteadas em genes que codificam fatores de transcrição permitiu identificar várias proteínas potencialmente envolvidas na regulação do metabolismo de glicogênio do fungo N. crassa. Dentre as proteínas, o fator de transcrição FLBC foi identificado como uma possível proteína regulatória do metabolismo de glicogênio. A linhagem mutante apresentou alterações no perfil de acúmulo de glicogênio e na expressão do gene gsn em relação à linhagem selvagem, quando submetidas a estresse térmico. Estudos preliminares realizados anteriormente em nosso laboratório mostraram severas alterações morfológicas na linhagem flbCKO, como reduzida capacidade de conidiação, com a presença de poucos microconídios, formação de hifas aéreas reduzidas, morfologia das extremidades das hifas alterada, aspecto e morfologia alterados das colônias e produção acentuada do pigmento melanina, indicando que a proteína FLBC desempenha importante papel no desenvolvimento do fungo. O fator de transcrição FLBC, objeto de estudo deste trabalho, é uma proteína homóloga às proteínas FlbC e FLE1 dos fungos Aspergillus nidulans e Podospora anserina, respectivamente, ambas envolvidas nos processos de conidiação e desenvolvimento dos fungos. O objetivo deste trabalho foi realizar uma caracterização funcional detalhada deste fator de transcrição em N. crassa. Análises de expressão gênica mostraram níveis elevados do transcrito flbC durante o crescimento vegetativo do fungo e após a indução do desenvolvimento assexual. A linhagem nocaute mostrou uma desregulação...
Keywords: Biotecnologia; Neurospora crassa; Glicogenio; Expressão gênica; Gene expression